Using Read, Cover, Remember, Retell (RCRR) Teaching Strategy Toward Reading Comprehension Achievemen - Arief Hadziq; Aminatul Afifah; Vella Fidia; Elen Elyana Elza; Shoni Musthofa (Departement of Mathematics Education, 2024)
The objective of this study is to determine whether a noteworthy disparity exists between students instructed using the One effective strategy for improving reading comprehension is the Read, Cover, Remember, Retell (RCRR) approach. Comparatively, conventional teaching methods are also utilized to teach reading comprehension achievement. This study was quantitative, utilizing an experimental method and employing an actual experimental design. Cluster random sampling was utilized for the sampling process in collecting the data. The population is 94 students, and the sample is 61 students. The data was acquired through Independent t-test analysis via SPSS 16, comparing the post-test results of the experimental and control groups results. The researcher's statistical analysis involved utilizing an independent t-test within SPSS 16 and concluded that the Sig (2-tailed) (0,001 <0.05). It indicates that there were no substantial differences between the experimental and control groups. So, the null hypothesis (Ho) was rejected, and the alternative idea (Ha) was accepted. The read, Cover, Remember, Retell (RCRR) strategy was significantly influenced in teaching reading comprehension achievement.